Politics, policies, and a human rights agenda for racialized minorities: The role of adult education. Issue 170 (12th September 2021) - Martin, Larry G.; Apugo, Danielle
Abstract: As we have witnessed under the Trump Administration, policies can negatively impact adults' livelihoods. Now more than ever, it is imperative that adult education organizations coalesce their resources and efforts to promote policies and agendas that serve our most vulnerable adult learners. This article will explore a framework to understand the historic struggle for social justice and governmental policies impacting adult education. It will also critically analyze how adult education research is poised to influence policy and how associations can partner for greater impact.